How preconditioning and pretensioning of grafts used in ACLigaments surgical reconstruction are influenced by their mechanical time-dependent characteristics: Can we optimize their initial loading state?. (March 2021) - Marchiori, Gregorio; Lopomo, Nicola Francesco; Bologna, Emanuela; Spadaro, Doriana; Camarda, Lawrence; Berni, Matteo; Visani, Andrea; Zito, Marianna; Zaffagnini, Stefano; Zingales, Massimiliano
Abstract: Purpose: Consensus about a pre-implant preparation protocol adaptable to any graft used in Anterior Cruciate Ligament reconstruction is still lacking. In fact, there is not agreement on reliable metrics that consider both specific graft dimensional characteristics, such as its diameter, and the inherent properties of its constitutive material, i.e. ligaments or tendons. Aim of the present study was to investigate and propose the applied engineering stress as a possible metrics. Methods: Preconditioning and pretensioning protocol involved groups of grafts with different section (10 or 32 mm 2 ) and materials (i.e. human patellar and hamstring tendons, and synthetic grafts). A 140 N load was applied to the grafts and maintained for 100 s. Initial stress and following stress-relaxation (a mechanical characteristic that can be related to knee laxity) were specifically analysed. Findings: Initial stress, ranging between 4 and 12 MPa, was affected primarily by the graft cross-section area and secondarily by the choice of the graft material. In terms of loss of the initial stress, stress-relaxation behaviour varied instead on a narrower range, namely 13–17%. Interpretation: Engineering stress can be identified as the correct metrics to optimize the initial state of each graft to avoid excessive stiffness, laxity or fatigue rupture phenomena. Highlights: Implement preconditioning/pretensioning protocol, and apply it to for Ligaments reconstruction. Mechanical test on Patellar and Hamstring ligaments about two different values of section. This study provided an important basis about the choice of graft in the treatment of Ligaments injury.